2011
DOI: 10.1002/ejoc.201100034
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of the (+)‐Antimycin A Family

Abstract: An asymmetric aldol reaction using Oppolzer's sultam has provided a practical and efficient synthetic route (15 steps, overall yield ca. 24 %) to 12 compounds of the Antimycin A family and deisovalerylblastmycin, which were obtained in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…62,63 The synthesis of naturally occurring (+)-6 was then investigated by the same research group a few years later, 64 and this report was followed by the syntheses of 6 and 7 by several other groups. 10 This route overcame the issues associated with previous attempts using an asymmetric aldol reaction by employing Oppolzer's sultam as a chiral auxiliary. Wu et al, however, reported a synthetic study of 6 with a 62% dilactone ring-closure yield in the presence of a C8 ester installed using TiCl 4 -mediated aldolization (Scheme 1).…”
Section: Chemical Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…62,63 The synthesis of naturally occurring (+)-6 was then investigated by the same research group a few years later, 64 and this report was followed by the syntheses of 6 and 7 by several other groups. 10 This route overcame the issues associated with previous attempts using an asymmetric aldol reaction by employing Oppolzer's sultam as a chiral auxiliary. Wu et al, however, reported a synthetic study of 6 with a 62% dilactone ring-closure yield in the presence of a C8 ester installed using TiCl 4 -mediated aldolization (Scheme 1).…”
Section: Chemical Synthesismentioning
confidence: 99%
“…Since their initial isolation in 1949, 1 antimycin-type depsipeptides have received considerable interest because of their potent and diverse biological activities. [9][10][11] It will also discuss the recent identication and characterization of hybrid nonribosomal peptide synthetase (NRPS)-polyketide synthase (PKS) assembly lines responsible for the biosynthesis of antimycin-type depsipeptides, 8,12 which has prompted the generation of a signicant number of new antimycin analogues. 2 More recently, several classes of antimycin-type depsipeptides have also been shown to have promising anti-cancer and anti-inammatory activities.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Recently, Tsunoda and co-workers completed the total synthesis of 12 components of antimycins. [17] In all cases, a dilactone ring between the O-5 and C-6 position was constructed to avoid γ-lactone formation. [18] The 3-formamidosalicylate group was introduced after dilactone ring construction.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, three biogenetically related compounds, antimycins A 1ab ( 3a / b ), A 2a ( 4 ) [ 16 ], and A 9 ( 5 ) [ 12 ], were identified by HR-TOF-MS and NMR data analyses and by comparison with other data in the literature. Unfortunately, the structural similarities of the inseparable mixtures, Compounds 3a / b , bearing a closely related acyl group, have made their separation via HPLC purification difficult.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that ANTs are produced by a polyketide synthase (PKS)/hybrid non-ribosomal peptide synthetase (NRPS) assembly line in a biosynthetic pathway [ 13 , 14 , 15 ]. Natural ANTs possess a unique nine-membered dilactone core conjugated with a 3-formyl aminosalicylic acid (FAS) moiety [ 16 ].…”
Section: Introductionmentioning
confidence: 99%